Pheochromocytoma-induced shock: a case report - Araújo, Stanley de Almeida; Carmo, Paula Alves Santos do; Paulino Júnior, Eduardo; Borges, Isabela Nascimento; Rocha, Luiz Otávio Savassi (Autopsy and Case Reports, 2012)
Because of its rarity, together with the variability and nonspecificity of its signs and symptoms, pheochromocytoma, a tumor arising from chromaffin cells, creates an unlucky paradox: it is often missed but only rarely found. Besides the association with arterial hypertension, often in the form of paroxysmal attacks, pheochromocytoma may also be associated, in up to 40% of cases, with orthostatic hypotension which, when present, provides a clue to the diagnosis of the tumor. Far more rare (about 2% of cases) is the clinical presentation in the form of shock, a possibility that, among other attributes, justifies the epithet “the great mimic” applied to the neoplasia. The authors report the case of a 51-year-old hypertensive woman whose death was erroneously attributed to septic shock. Autopsy disclosed an unsuspected left adrenal bulky pheochromocytoma with areas of hemorrhage and extensive central necrosis, pronounced pulmonary edema, left ventricular mural thrombus, and histological evidence of acute myocardial injury.